(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Cancer is one of the leading causes of mortality worldwide, with an increasing global burden and significant disparities in its incidence and treatment. Hybrid nanoparticles (LHNPs) represent a cutting-edge advancement in nanotechnology-based drug delivery for cancer therapy. These nanoparticles combine lipid carriers' biocompatibility with polymeric nanoparticles' structural stability, resulting in improved drug solubility, controlled release, and enhanced tumour targeting. LHNPs enhance drug delivery to cancer sites through both passive and active targeting strategies, leveraging the enhanced permeability and retention (EPR) effect along with ligand-based targeting to increase drug concentration at tumor locations. The formulation of LHNPS involves various preparation techniques, including high-pressure homogenisation, solvent evaporation, and nanoprecipitation, ensuring stability and optimal drug loading efficiency. Their structural composition consists of a lipid matrix encapsulating a hydrophilic or hydrophobic drug core, allowing versatile drug delivery applications. Characterisation techniques such as dynamic light scattering (DLS), zeta potential analysis, and transmission electron microscopy (TEM) assess particle size, surface charge, and morphology, which are crucial for therapeutic efficacy. Despite their advantages, challenges such as large-scale manufacturing, long-term stability, and potential cytotoxicity require further research. The integration of LHNPs into cancer therapy offers a promising approach to overcoming conventional treatment limitations, enhancing patient outcomes with reduced systemic toxicity.